Maltodextrin's effect on the performance of elite mountain biking athletes during simulated competition and on power output at the ventilatory threshold - Maneck Malfatti, C. R.; Fontana de Laat, E.; Tramontin Soler, L.; Bronkhorst, I. W.; Pacheco, C. V.; Irineu Bortoli Funez, E.; Pavlak, J. L.; da Silva, L. A.; Osiecki, R. (Human Movement, 2011)
To aim of this study was to analyze the effects of maltodextrin supplementation on cardiovascular and performance parameters during simulated Mountain Biking (MTB) competition as well as the cardiorespiratory and blood glucose (BG) response to a maximal test performed in a laboratory on elite MTB athletes. Methods. A total of eight male bikers [age: 28.4 ± 10.6 years; body fat: 9.46 ± 3.76 %; VO2max: 55.31 ± 4.7 mL/kg/min], participated in a double-blind study. The athletes received maltodextrin supplementation (1g/kg) or a placebo (light tangerine juice) 20 min before competition (seven 2 km laps) or before a laboratory maximal test. An incremental exercise test on a cycloergometer was performed to find any alterations in maximal HR, Watts max, VO2max, VEmax, and VO2 at the ventilatory threshold (VT), using a gas exchange analyzer. Comparisons between the simulated competition and laboratory variables (maltodextrin vs. placebo) were made using ANOVA and a two-tailed paired Student's t-test, where p < 0.05 was considered statistically significant. Results. Maltodextrin supplementation reduced 26 s in the mean time spent on completing all laps (Maltodextrin: 9 min and 16 s vs. placebo: 9 min and 35 s; p < 0.05). In laboratory testing, maltodextrin raised BG during exercise (Maltodextrin: 104.1 ± 20.9 mg/dL vs. placebo: 88.2 ± 5.3 mg/dL; p < 0.05), power output at the ventilatory threshold (Maltodextrin: 260.8 ± 12.9 vs. placebo: 150.5 ± 8.7; p < 0.05) but had no effect on cardiorespiratory variables. Conclusion. Maltodextrin was found to enhance athletic performance during MTB competition, showing that it can play an important role in supplementation strategies for these competitors.